Physical Fitness of New Class X Students of SMA Negeri 1 Ngimbang Lamongan - Zoki, Achmed (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to determine the level of physical fitness of new students in class X of SMA Negeri 1 Ngimbang Lamongan at the beginning of the 2023/2024 academic year. This type of research is descriptive, using a survey method and data collection through the TKJI test. The sampling technique was purposive sampling, namely, new students in class X with 295. From the results of the study, the overall average value was 16.7, with details of 1. 0% or no students were in the outstanding category, 2. 35.6% or 105 students were in the excellent category, 3. 39.7% or 117 students were in the moderate category, 4. 23% or 68 students were in the less category, 5. 1.7% or five students were in the significantly smaller category. With the results obtained based on an average value of 16.7 and a percentage value of 39.7%, it can be concluded that new students in class X of Ngimbang State High School for the 2023/2024 academic year are in the moderate classification category. The results obtained can be used as a reference for physical education and sports teachers in implementing physical education and sports learning in the future so that the teaching carried out is appropriately on target and can improve physical fitness based on the abilities of each student.